The Peruvian species of Cristaria (Malveae, Malvaceae): taxonomic revision, chromosome counts, and breeding system - Schneider, Julio V. (Phytotaxa, 2013)
Cristaria (Malvaceae) contains about 20 species distributed in Chile, Argentina, and Peru. Most of the species are confined to the Chilean Atacama desert, two species are shared with Argentina, and three species had been reported for Peru. Of the three species previously cited for Peru, only Cristaria multifida is recognized here. One new subspecies is described (Cristaria multifida subsp. moquipana) and a lectotype for Sida pterosperma is here designated. Nomenclatoral and taxonomic notes as well as a key to the two subspecies of Cristaria multifida are presented. Additionally, chromosome numbers for Cristaria multifida (2n = 12) are reported for the first time. Based on pollen-ovule ratios, C. multifida is considered facultatively autogamous to facultatively xenogamous.